Stroke prevention-surgical and interventional approaches to carotid stenosis - Kumar Rajamani; Seemant Chaturvedi (Indian Journal of Neurosurgery)
Extra cranial carotid artery stenosis is an important cause of stroke, which often needs treatment with carotid revascularization. To prevent stroke recurrence, carotid endarterectomy (CEA) has been well-established for several decades for symptomatic high and moderate grade stenosis. Carotid stenting is a less invasive alternative to CEA and several recent trials have compared the efficacy of the 2 procedures in patients with carotid stenosis. Carotid artery stenting has emerged as a potential mode of therapy for high surgical risk patients with symptomatic high-grade stenosis. This review focuses on the current data available that will enable the clinician to decide optimal treatment strategies for patients with carotid stenosis.